2019
DOI: 10.1108/pm-04-2018-0026
|View full text |Cite
|
Sign up to set email alerts
|

User-focused office renovation: a review into user satisfaction and the potential for improvement

Abstract: Purpose This paper highlights the importance of user satisfaction in office renovation. A user-focussed renovation approach can enhance user satisfaction in offices and their functional quality while meeting energy performance goals. The purpose of this paper is to investigate users’ needs and the physical and psychological factors affecting user satisfaction, as input to office renovation projects. Design/methodology/approach The selected articles are collected from Scopus, ScienceDirect and Google Scholar.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 91 publications
0
26
0
Order By: Relevance
“…Digital questionnaires, and to a certain extent hard-copy questionnaires, were used to collect data about the user satisfaction of the employees in the five buildings. Figure 2, constructed by Kwon et al (2019b), illustrates the main ten factors of user satisfaction with physical and psychological comforts, based on the studies by De Been and Beijer (2014), Vischer (2008), Tucker and Smith (2008) and Leifer (1998). The ten factors are classified according to three dimensions: physical comfort, functional-influential comfort and psychological comfort.…”
Section: Methodology 21 Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital questionnaires, and to a certain extent hard-copy questionnaires, were used to collect data about the user satisfaction of the employees in the five buildings. Figure 2, constructed by Kwon et al (2019b), illustrates the main ten factors of user satisfaction with physical and psychological comforts, based on the studies by De Been and Beijer (2014), Vischer (2008), Tucker and Smith (2008) and Leifer (1998). The ten factors are classified according to three dimensions: physical comfort, functional-influential comfort and psychological comfort.…”
Section: Methodology 21 Study Designmentioning
confidence: 99%
“…However, De Been and Beijer (2014) included combi and flex office types in their study. Kwon et al (2019b) found that prominent psychological variables are privacy, concentration, communication, social contact and spatial comfort (territoriality).…”
Section: Introductionmentioning
confidence: 99%
“…There are several variables used, in accordance with the proposed hypothesis and also those in the DeLone and McLean model, then several variables that can be used for indicators that have an influence There are 6 variables in the preparation of the questionnaire, these 6 items have been implemented by several researchers [18][19][20][21] :…”
Section: Variable and Indicatorsmentioning
confidence: 99%
“…In their study on the importance of user satisfaction in office renovation, Kwon, Remøy, and Van Den Dobbelsteen (2019), state that a user-focused renovation approach can promote user satisfaction in offices and their functional while quality meeting energy performance goals. They identify ten influential factors (e.g., thermal comfort, air quality, lighting, noise, user control, privacy, concentration, communication, social contact, and spatial comfort), divided into physical comfort, functional, and psychological comfort.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…It is considered a place where managers from the corporate world tend to scout for fresh talent and environmental traits, accelerating communication flow (Williams & LaBrie, 2015). Furthermore, Kwon et al (2019) believe that employee satisfaction and productivity are among the main interests of employers. They find that privacy, concentration, communication, social contact, and territoriality significantly determine psychological satisfaction measures.…”
Section: Theoretical Frameworkmentioning
confidence: 99%